Loss-given-default and macroeconomic conditions - Benjamin Galow; Oana-Maria Georgescu; Aurea Ponte Marques (European Central Bank (ECB), 2024)
We study the sensitivity of the realised loss-given-default (LGD) to macroeconomic conditions by exploring Global Credit's confidential dataset on observed cash flows from defaulted loans. Given the prolonged duration of loan recovery, spanning several years, and the potential for macroeconomic fluctuations during this time frame, our study explores whether the sensitivity of realised LGD to macroeconomic conditions varies based on the timing of cash flows. We find that, regardless of the cash flow timing, the sensitivity of the LGD to macroeconomic conditions is higher for real-estate secured loans than for unsecured loans. The most relevant macroeconomic variables for the secured LGD are the unemployment rate and stock returns, followed by house price growth and the change in the long-term interest rate. For unsecured loans, real GDP growth and stock returns are the most relevant predictors. These results may be relevant for both micro and macroprudential policymakers by informing on the procyclicality of risk parameters and bank capital requirements.
Keywords: G21; G32; G33; E32; 330; Banks; Financial Risk; Bankruptcy; Business Fluctuations